Pengaruh Task Technology Fit (TTF) terhadap Performance Impact Penggunaan Rekam Medis Elektronik di RS Adi Husada Kapasari Surabaya - Kurniasari, Dewi; Kurniawan, Afif; Putri, Linta Meyla (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: The implementation of Electronic Medical Records (RME) in hospitals aims to improve the efficiency and quality of health services. The implementation of RME needs to be adjusted to the task requirements and user characteristics in order to provide optimal benefits. The Task-Technology Fit (TTF) method can be used to analyze the fit between information technology and the tasks it supports. Aims: to determine the relationship between Task Technology Fit and Performance Impact. Electronic Medical Records at Adi Husada Hospital Kapasari Surabaya. Methods: This research uses a quantitative approach with a survey method on a sample of RME users in hospitals. Data was collected through questionnaires and analyzed using the Pearson correlation test Results: The research results show that the use of Electronic Medical Records (RME) has a significant effect on user performance. This is because the RME application is easy for users to understand and learn, and is able to provide the latest information according to patient service needs. With the ease of use and suitability of the RME application features to task requirements, it has a positive impact on improving the performance of officers who use the application in hospitals. Conclusion: Implementation of Electronic Medical Records (RME) in hospitals according to the Task-Technology Fit (TTF) method. The characteristics of RME and its suitability to task requirements have a positive impact on officer performance. Hospitals need RME development and training to improve efficiency and quality of service.